THE ROLE OF PROSODY OF NATIVE LANGUAGE WHILE LEARNING A FOREIGN LANGUAGE - L. S. Kasyanenko; L. M. Mitrofanenko (Гуманитарные и юридические исследования)
The article is devoted to the problem of prosody of native language, resulting from the interaction of phonetic systems of native and non-native languages in bilingual speech while learning a foreign language, that is, in a situation of artificial (classroom) multilingualism. The article includes definition of concepts such as phonetics, interference and prosodic interference. The reasons for the differences between the original and interfered in the process of learning language are considered and analyzed.